Financial development and environmental quality nexus: Testing the double materiality hypothesis - Joof, Foday; Adaoglu, Cahit (Taylor & Francis Inc, 2024)
A novel paradigmatic concept has recently been introduced in the financial development-environmental quality nexus, referred to as the double materiality concept. This concept proposes that not only is financial development significant for the environment, but the environment also has a significant impact on financial development. We examine this financial development-environmental quality nexus by proposing and empirically testing the double materiality hypothesis. The cross-sectional Autoregressive Distributed Lag estimations and the Dumitrescu-Hurlin causality test are applied in the top-ten CO2 emitting countries over the period 1990-2018. We empirically confirm the validity of the double materiality hypothesis in these countries. Specifically, the cross-sectional Autoregressive Distributed Lag estimation results show that financial development exhibits a positive impact on the level of CO2 whilst the level of CO2 emissions hinders financial development in the top-ten CO2 emitters. Similarly, the causality test results show that there is a bidirectional association between the financial development and the level of CO2 emissions. Thus, regulatory authorities should take proactive approaches by assessing the externalities of climate-related risks and the potential channels that may trigger systemic risks.
Keywords: Double materiality hypothesis; financial development; environmental quality; CO2 emissions; climate risks; renewable energy; CS-ARDL; causality; cointegration